Comparative Notes on the use of Commercial Litigation Funding in Insolvency: Australia and South Africa - Sulette Lombard; Andre Boraine (Potchefstroom Electronic Law Journal, 2023)
This article explores the application of third-party litigation funding (TPLF), also referred to as commercial litigation funding, in insolvency litigation by way of a comparison of the legal position in Australia and South Africa. It proposes that TPLF could offer significant benefits by enabling liquidators of insolvent estates to pursue and enforce claims through civil proceedings with the aim of swelling the assets of the insolvent estate, ultimately to the advantage of the creditors. Since both jurisdictions share elements of English law, both were confronted with the English law doctrines of champerty and maintenance initially being regarded as impediments to the development and/or use of TPLF. Currently, and mainly due to developments in terms of case law, the concept of TPLF has in principle been accepted in both jurisdictions. However, in Australia the development originally transpired in the field of insolvency litigation. In South Africa the context was more in the confines of general litigation. It is submitted that the South African system could benefit by considering various aspects of the Australian system regarding the use of TPLF in insolvency litigation. It remains a question whether or not the respective systems would benefit by adopting comprehensive regulatory measures to regulate TPLF.